Social Responsibility and bioethics in higher education: transversal dialogues - Carlotto, Ivaní Nadir (2021)
This chapter seeks to analyse the interface between social responsibility (SR) concepts in higher education (HE) and its connection with the bioethical approach. The idea of SR is an intrinsic aspect of the bioethical paradigm, and its role is increasingly recognized in several areas of knowledge due to its transdisciplinary and transversal reach. Bioethics, in turn, joins the concept of SR to reflect on the plural and salutogenic character of health, considering the social context in which decisions are made and the well-being of individuals. The philosophical foundations of the SR and Bioethics paradigms consider the individual as a necessary element for effective decision-making about their health and become essential to validate and implement the primary interventions carried out in health promotion (HP). In line with the concepts of SR and bioethics, sustainability emerges, which deals with human dignity and well-being in an approach of a fundamentally ethical character. Its greatest example is the 17 Sustainable Development Goals of the 2030 Agenda. The concepts of SR, bioethics and sustainability provide the intersection with several determinants that impact social, organizational and public policy decisions. Research involving bioethics and SR seeks to recognize and validate the transversal concepts necessary for interdisciplinarity in a perspective of joint construction to implement effective policies related to SR.